An analysis of college and career readiness emphasis in ESSA state accountability plans - Donald G. Hackmann; Joel R. Malin; Debra D. Bragg (Arizona State University, 2019)
This study examined the extent and manner in which college and career readiness (CCR) is emphasized in Every Student Succeeds Act (ESSA) state accountability plans. We analyzed 52 plans (50 states, DC, Puerto Rico) using frameworks developed by Cook-Harvey, Darling-Hammond, Lam, Mercer, and Roc (2016) and Dowd and Bensimon (2015). Findings disclose significant variation, with CCR featuring prominently in some plans and receiving cursory mention in others. Most states identified CCR components as part of their school quality or student success indicators but few used ESSA to restructure their state initiatives to address persistent inequities. Even states making CCR a central feature typically applied color-blind approaches, addressing CCR for all students rather than developing CCR plans to address inequitable outcomes for student subgroups.